Effect of Microcredit on Agricultural Output: Evidence from Rural Bangladesh (Journal of Asian Development Studies, 2013)
This research reveals the effect of microcredit on agricultural output produced by small farmers of Khulna district in Bangladesh. Rice production is used as proxy of agricultural output as most of the farmers are engaged in rice production in Bangladesh. The sample size was restricted to a total of 80 farmers out of which 40 farmers have been selected from each of the microcredit receiving and non-receiving groups, on the basis of random sampling technique. Cobb-Douglas production function was used to estimate the effect of various inputs on farm output (rice production). A multiple regression model was also used to measure the effect of the socio-economic determinants affecting farm output. To check socio-economic homogeneity between microcredit beneficiary and non-beneficiary group, t-ratio and z-score were used. Result of the production function shows that marginal effect of capital and labor are positive but less than one which are statistically significant at 1% and 5% level respectively. Microcredit beneficiaries produce 15% more rice than that of non-beneficiary group which is also statistically significant at 1% level. Among socio-economic determinants, experience and fulltime farming affect farm output positively when it is estimated jointly. These two variables are also significant in microcredit receiving category. Poor farmers face high interest rate and consume microcredit as they get credit prior to stating farming. They are to start repaying loan after the next week of receiving but get output after cropping period which is about 6 months. Thus they get less benefit as credit mechanism doesn’t incorporate gestation period. So, credit system should be well developed incorporating gestation period to reflect aspirations of the small farmers that benefit them.